Strengthening the Revitalization and Refoundationalization of the Pancasila Philosophy as National Character Education - Sumarna, Andri; Haryono, Merda Budi; Fauzi, Sudar; Emuh, Dadang; Irawan, Yusuf (Universitas Pahlawan Tuanku Tambusai, 2025)
The philosophy of Pancasila as the final ideology and foundation for the life of the Indonesian nation and state has its roots in the personality and identity of the Indonesian people for hundreds of years, with its values embedded since the era of the archipelago’s kingdoms. The founders of the republic fought for independence by establishing Pancasila as the guiding principle for societal, national, and state life, as emphasized by Bung Karno, who even proposed at the UN General Assembly on September 30, 1960, that Pancasila be applied in international relations. However, in recent times, its existence as a national ideology has been questioned, making it essential to revitalize and reestablish Pancasila so that Indonesia can interact with dignity among nations, stand firmly amidst globalization’s risks, conflicts, and fierce competition, and ensure that future generations inherit and uphold Pancasila as a pillar of national character education for centuries to come.